Performance of Impure Calcined Clay as a Pozzolan in Concrete. Issue 2 (February 2021) - Jafari, Khashayar; Rajabipour, Farshad
Supplementary cementitious materials (SCMs) are natural or industrial by-product materials which are used to improve the performance, durability, and sustainability of concrete mixtures. Motivated by the recent reports on shortage of conventional SCMs, impure calcined clays (CCs) are receiving attention as abundant alternative pozzolans for concrete. In this study, a clay slurry resulting from washing aggregates in a commercial sand and gravel pit was investigated. This source clay was dried and calcined, and the properties and pozzolanic performance of the resulting CC was evaluated. It was observed that despite having a large (>50%wt.) inert quartz content, the CC met all ASTM C618-19 (AASHTO M295) requirements for natural pozzolan. A pavement-grade concrete mixture containing 20%CC as a cement replacement (by weight) produced desired workability and fresh and hardened air content. Strength development was slightly below the control. The use of CC improved the durability of concrete with respect to chloride penetration, alkali–silica reaction, and drying shrinkage in comparison with a control (100% Portland cement) mixture. In addition, ternary limestone-calcined clay–cement and slag-calcined clay–cement mortar mixtures showed excellent strength development while replacing nearly 50% of the Portland cement.